2006
DOI: 10.1375/ajgc.16.2.211
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives Regarding the Role of School Psychologists: Perceptions of Teachers, Principals, and School Psychologists in Victoria, Australia

Abstract: School psychologists have a unique and multifaceted role within schools and must work with a variety of stakeholders. Therefore, it is important to explore and understand the perspectives of other educational professionals regarding the roles of school psychologists. This study examined the perspectives of principals (N = 21), teachers (N = 86), and school psychologists (N = 81) regarding what they believe should be the role of school psychologists. Participants were working in Catholic, Independent, and Gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…School counselors reported undertaking a wide range of daily tasks with one-fifth of their time spent on administration. This confirms the multispecialist role of the school counselor [ 24 ].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…School counselors reported undertaking a wide range of daily tasks with one-fifth of their time spent on administration. This confirms the multispecialist role of the school counselor [ 24 ].…”
Section: Discussionsupporting
confidence: 78%
“…This disparity is also common in the United States [ 23 ], which may reduce the school counselors’ capacity to proactively identify students in need [ 12 ]. Australian school counselors also occupy a multispecialist role as they conduct psychometric assessments, deliver training to staff, and liaise with parents, teachers, and external services [ 24 ]. These demands can lead to a sense of role ambiguity [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from the United States (Bodenhorn, 2006;Gilman and Gabriel, 2004;Kaplan, 1995;Kirchner and Setchfield, 2005), Canada (Lehr et al, 2007), the United Kingdom (Voskuijl and Evers, 2007) and Australia (Thielking and Jimerson, 2006) have explored the role of the school counsellor and the varied perspectives of counsellors, principals and teachers regarding the role of the school counsellor. In general, there seems to be a lack of understanding of what the counsellor could do and how the counsellor is expected to act, particularly in relation to situations that were ethically wrought.…”
Section: The Role Of the School Counsellormentioning
confidence: 99%
“…Alternatively, while it has been reported that school psychologists collaborate with teachers and other professionals both within and outside of a school setting, research on the mechanisms of school psychologist collaboration is scarce. What we do know is that teachers and principals often desire the school psychologist to engage in more information sharing, but that this can place a school psychologist in a tricky ethical and professional dilemma (see Thielking & Jimerson, 2006). Such competing demands for information from a range of stakeholders has been aptly described as a 'complex balancing act' (Glosoff & Pate, 2002).…”
mentioning
confidence: 99%